Molecular epidemiology of fluoroquinolone resistant Salmonella in Africa: A systematic review and meta-analysis. - Getachew Tadesse; Tesfaye S Tessema; Getenet Beyene; Abraham Aseffa (PLoS ONE)
Background Wide-ranging evidence on the occurrence of fluoroquinolone (FQ) resistance genetic determinants in African Salmonella strains is not available. The main objectives of this study were to assess the heterogeneity, estimate pooled proportions and describe the preponderance of FQ-resistance determinants in typhoidal and non-typhoidal Salmonella (NTS) isolates of Africa. Methods Genetic and phenotypic data on 6103 Salmonella isolates were considered. Meta- and frequency analyses were performed depending on the number of studies by category, number of isolates and risks of bias. A random effects model was used to assess heterogeneity and estimate pooled proportions. Relative and cumulative frequencies were calculated to describe the overall preponderance of FQ-resistance determinants in quinolone resistant isolates. Results The pooled proportion of gyrA mutants (Salmonella enterica serovar Typhi, Salmonella enterica serovar Typhimurium, and Salmonella enterica serovar Enteritidis) was estimated at 5.7% (95% Confidence interval (CI) = 2.6, 9.8; Tau squared (T2) = 0.1105), and was higher in S. Typhi than in S. Typhimurium (odds ratio (OR) = 3.3, 95%CI = 2, 5.7). The proportions of each of gyrB and parC mutants, and strains with Plasmid Mediated Quinolone Resistance genes (qnrA, qnrB and qnrS) were low (≤ 0.3%). Overall, 23 mutant serotypes were identified, and most strains had mutations at codons encoding Ser83 and Asp87 of gyrA (82%, 95%CI = 78, 86). Conclusions Mutations at gyrA appear to account for ciprofloxacin non-susceptibility in most clinical Salmonella strains in Africa. The estimates could be harnessed to develop a mismatch-amplification mutation-assay for the detection of FQ-resistant strains in Africa.